TRAIT AND FACTOR GROUP COUNSELING IN IMPROVING STUDENTS’ CAREER PLANNING - Febrianto, Qori; Khairun, Deasy Yunika; Nurmala, Meilla Dwi; Kim, Jane Jihye (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2024)
The purpose of this research is to determine the effect of providing trait and factor group counseling on improving student career planning. The method used in this research is experimental times series design with a population of 47 students and a research sample of 6 students. The data collection method in this research used a student career planning questionnaire consisting of 23 statements with a reliability value (rcount) of 0.868. Based on the research results, pre-test results 1, 2, 3 were obtained which showed that the career planning of students in the research sample was in the low category. Meanwhile, the post-test results 1, 2, 3 show that students’ career planning has increased and is in the high category. So, it can be concluded that providing trait and factor group counseling has an influence on improving the career planning of student.